Gallic acid downregulates matrix metalloproteinase-2 (MMP-2) and MMP-9 in human leukemia cells with expressed Bcr/Abl - Chen, Ying-Jung; Chang, Long-Sen (Molecular nutrition & food research, 2012)
Scope The aim of the present study was to explore the signaling pathways associated with gallic acid induced matrix metalloproteinase‐2 (MMP‐2)/MMP‐9 downregulation in human leukemia K562 cells. Methods and results Unlike the insignificant effect on human Bcr/Abl‐negative leukemia U937 cells, gallic acid attenuated invasion of human Bcr/Abl‐positive leukemia K562 cells with characteristic of decreased protein expression and mRNA levels of MMP‐2 and MMP‐9. Gallic acid induced β‐TrCP upregulation evoked Bcr/Abl degradation in K562 cells, while overexpression of Bcr/Abl attenuated gallic acid induced MMP‐2/MMP‐9 downregulation. Overexpression of Bcr/Abl restored the levels of phospho‐ERK and phospho‐Akt but not JNK phosphorylation in gallic acid treated K562 cells. Gallic acid treatment repressed Akt/ERK‐mediated c‐Fos phosphorylation and JNK1‐mediated ATF‐2 phosphorylation. c‐Jun inactivation was mediated through gallic acid induced Akt/ERK and JNK inactivation. Knockdown of c‐Fos, c‐Jun, and ATF‐2 by siRNA and luciferase promoter assay reflected that c‐Jun/ATF‐2 and c‐Jun/c‐Fos were, respectively, responsible for MMP‐2 and MMP‐9 expression in K562 cells. Chromatin immunoprecipitating assay showed that gallic acid reduced the binding of c‐Jun/ATF‐2 and c‐Jun/c‐Fos with promoter region of MMP‐2 and MMP‐9 genes, respectively. Conclusion Our data indicate that MMP‐2 and MMP‐9 downregulation in gallic acid treated K562 cells are mediated through suppression of JNK1‐mediated c‐Jun/ATF‐2 and Akt/ERK‐mediated c‐Jun/c‐Fos pathways, respectively.